2022-RA-967-ESGO Endometrial cancer: agreement between microsatellite instability in immunohistochemistry and molecular biology?. (20th October 2022) - Gennigens, Christine; Dheur, Adriane; Bours, Vincent; Delbecque, Katty; Gonne, Elodie; Pleyers, Clemence; Seidel, Laurence; Streel, Sylvie; de Cuypere, Marjolein; Goffin, Frederic; Lovinfosse, Pierre; Kakkos, Athanasios; et al.
Abstract : Introduction/Background: Endometrial carcinoma (EC) is the most common cancer of the female genital tract in developed countries. Microsatellite instability (MSI), that represents 30% of EC, is an important prognostic and predictive biomarker. This status is assessed by detection of loss of MMR genes' proteins by immunohistochemistry (IHC) or by molecular biology. We aimed to compare the agreement between MSI status in IHC and molecular biology. Methodology: Between January 2019 and December 2021, we conducted a monocentric retrospective study of 166 patients treated for EC (all stages) at the CHU of Liège. Sixty-seven patients were excluded. The remaining 99 patients had a complete IHC and molecular analysis for MSI. McNemar's test and a Kappa of Cohen coefficient were used to evaluate the agreement between the 2 methods. Results: The McNemar's test demonstrated 41.4% and 39.4% of MSI in IHC and molecular biology, respectively ( p= 0.81). There were ten tumors with false-positive staining in IHC and MSS in molecular biology (specificity of 75.6%). Moreover, there were eight tumors with false-negative IHC but MSI-H in molecular analysis (sensitivity of 85.2%). The agreement between MSI in IHC and molecular analysis was 81/99 (81.8%) patients. The Kappa of Cohen coefficient was 0.62 (IC95%: 0.47–0.78), confirming the agreement between both techniques. Conclusion: The methods of testing MSI by IHC and molecular biology are clearly concordant. Presence of MSI in IHC can be considered as a reliable surrogate test for MSI molecular status. Moreover, IHC testing is quicker, easier to perform and less expensive. Nevertheless, based on a 25% and 15% rate of false positivity and negativity respectively, consideration should be given to confirm MSI IHC status for all patients by molecular analyses.